Biomimetic Syntheses of the Flindersial Alkaloids - Vallakati, Ravikrishna; May, Jeremy A. (Synlett, 2012)
The flindersial alkaloids have a potentially novel mechanism for antimalarial activity. The recently disclosed flinderoles were postulated to be derived through dimerization of the natural product borrerine in a manner similar to their structural isomers, the borreverines. Recent work by the authors has shown that the flindersial alkaloids share a common biosynthetic origin to that of borrerine. The application of this insight has resulted in the synthesis of naturally occurring flindersial alkaloids with controlled formation of the structural isomer. Only three synthetic steps from tryptamine are needed for any of the natural products.
Keywords: natural products; alkaloids; biomimetic synthesis; tandem reactions; regioselectivity